Molecular detection of Histoplasma capsulatum in organ samples from bats randomly captured in urban areas of Araraquara, São Paulo state, Brazil - Ruiz-Muñoz, Jessica A.; Rodríguez-Arellanes, Gabriela; Ramírez, José A.; Carreto-Binaghi, Laura E.; Fusco-Almeida, Ana M. [UNESP]; Mendes-Giannini, Maria J. S. [UNESP]; García-Pérez, Blanca E.; Taylor, Maria L. (Cambridge University Press (CUP), 2024)
The mycosis histoplasmosis is also considered a zoonosis that affects humans and other mammalian species worldwide. Among the wild mammals predisposed to be infected with the etiologic agent of histoplasmosis, bats are relevant because they are reservoir of Histoplasma species, and they play a fundamental role in maintaining and spreading fungal propagules in the environments since the infective mycelial phase of Histoplasma grows in their accumulated guano. In this study, we detected the fungal presence in organ samples of bats randomly captured in urban areas of Araraquara City, São Paulo, Brazil. Fungal detection was performed using a nested polymerase chain reaction to amplify a molecular marker (Hcp100) unique to H. capsulatum, which revealed the pathogen presence in organ samples from 15 out of 37 captured bats, indicating 40.5% of infection. Out of 22 Hcp100-Amplicons generated, 41% corresponded to lung and trachea samples and 59% to spleen, liver, and kidney samples. Data from these last three organs suggest that bats develop disseminated infections. Considering that infected bats create environments with a high risk of infection, it is important to register the percentage of infected bats living in urban areas to avoid risks of infection to humans, domestic animals, and wildlife.
Keywords: Bats; H. capsulatum; Hcp100 marker; Histoplasmosis; Nested PCR